2015
DOI: 10.1530/jme-15-0011
|View full text |Cite
|
Sign up to set email alerts
|

IL6 induces TAM resistance via kinase-specific phosphorylation of ERα in OVCA cells

Abstract: About 40-60% of ovarian cancer (OVCA) cases express ERa, but only a small proportion of patients respond clinically to anti-estrogen treatment with estrogen receptor (ER) antagonist tamoxifen (TAM). The mechanism of TAM resistance in the course of OVCA progression remains unclear. However, IL6 plays a critical role in the development and progression of OVCA. Our recent results indicated that IL6 secreted by OVCA cells may promote the resistance of these cells to TAM via ER isoforms and steroid hormone receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Strikingly, ER qPLEX-RIME under full estrogenic conditions demonstrated that increased association between ER and STAT3 was the only significant change in the ER complex following IL6induced phosphorylation of STAT3 (Figures 2A, S2A, and S2B). In contrast to ovarian cancer (Wang et al, 2015), Ser167 phosphorylation of ER was not induced by IL6 (Figure S2C). qPLEX-RIME of STAT3 showed that IL6 also increased the association between STAT3 and several well-known ER-associated factors such as FOXA1 and nuclear receptor coactivator 3 (NCOA3) (Figures 2A and S2B).…”
Section: Activated Stat3 Associates With the Er/foxa1 Complex On Chromatinmentioning
confidence: 87%
“…Strikingly, ER qPLEX-RIME under full estrogenic conditions demonstrated that increased association between ER and STAT3 was the only significant change in the ER complex following IL6induced phosphorylation of STAT3 (Figures 2A, S2A, and S2B). In contrast to ovarian cancer (Wang et al, 2015), Ser167 phosphorylation of ER was not induced by IL6 (Figure S2C). qPLEX-RIME of STAT3 showed that IL6 also increased the association between STAT3 and several well-known ER-associated factors such as FOXA1 and nuclear receptor coactivator 3 (NCOA3) (Figures 2A and S2B).…”
Section: Activated Stat3 Associates With the Er/foxa1 Complex On Chromatinmentioning
confidence: 87%
“…Current interest in the EOC field is focused on the importance of intercellular cross talk mediated by soluble and insoluble factors between the EOC tumor and stromal cells during development, progression, and evolution of drug-resistance [1618]. The EOC tumor microenvironment includes recruited host cells ( i.e ., endothelial cells, fibroblasts, and macrophages) that communicate with tumor cells and often are re-educated to supply functions which enhance metastasis, vascularization, and immuno-evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Serine 167 of ERα has been studied for many years. Phosphorylation of this site could activate and promote ERα-dependent transcription and cellular proliferation and is attributed to increased resistance to tamoxifen treatment [24][25][26]. Various studies have shown that increased Ser167 phosphorylation correlates with a poor prognosis in different cancer types [27,28].…”
Section: Tmem97/σ2 Receptor Activates Erα Independent Of Estrogen And...mentioning
confidence: 99%